Heard but not seen: Comparing bat assemblages and study methods in a mosaic landscape in the Western Ghats of India. Issue 8 (23rd March 2018) - Wordley, Claire F. R.; Sankaran, Mahesh; Mudappa, Divya; Altringham, John D.
Abstract: We used capture (mist‐netting) and acoustic methods to compare the species richness, abundance, and composition of a bat assemblage in different habitats in the Western Ghats of India. In the tropics, catching bats has been more commonly used as a survey method than acoustic recordings. In our study, acoustic methods based on recording echolocation calls detected greater bat activity and more species than mist‐netting. However, some species were detected more frequently or exclusively by capture. Ideally, the two methods should be used together to compensate for the biases in each. Using combined capture and acoustic data, we found that protected forests, forest fragments, and shade coffee plantations hosted similar and diverse species assemblages, although some species were recorded more frequently in protected forests. Tea plantations contained very few species from the overall bat assemblage. In riparian habitats, a strip of forested habitat on the river bank improved the habitat for bats compared to rivers with tea planted up to each bank. Our results show that shade coffee plantations are better bat habitat than tea plantations in biodiversity hotspots. However, if tea is to be the dominant land use, forest fragments and riparian corridors can improve the landscape considerably for bats. We encourage coffee growers to retain traditional plantations with mature native trees, rather than reverting to sun grown coffee or coffee shaded by a few species of timber trees. Abstract : We compare the efficacy of mist‐netting and acoustic recording to characterize a bat community in a biodiversity hotspot in south India. We use these methods to compare relatively undisturbed forest with a variety of habitat found in agricultural areas such as tea and coffee plantations, and forest fragments.